DO INERTIAL ELECTRIC CHARGES RADIATE WITH RESPECT TO UNIFORMLY ACCELERATED OBSERVERS - Matsas, GEA (Plenum Publ Corp, 1994)
We revisit the long standing problem of analyzing an inertial electric charge from the point of view of uniformly accelerated observers in the context of semi-classical gravity. We Choose a suitable set of accelerated observers with respect to which there is no photon emission coming from the inertial charge. We discuss this result against previous claims.